The essential care required by stroke survivors and families: an ethnography study - Kartika Setia Purdani; Somporn Rungreangkulkij (PAGEPress Publications, 2024)
From a cultural point of view, ethnographic research was needed to understand the essential care of stroke survivors and their families. Half of stroke survivors were dependent on family caregivers during neuroplasticity time, which could raise several burdens for both. This study aimed to analyze the essential care required for stroke survivors and their families. Focus ethnography design was employed with 64 participants selected purposively. The data collection methods were observation, in-depth interviews, and Focus Group Discussion (FGD). The techniques used were writing field notes for the content analysis, using thematic analysis to analyze data, and using COREX 32-items for reporting qualitative studies.The six themes identified were i) unclear information before discharge planning; ii)clear information from community nurses; iii) family brotherhood; iv) home visits; v) government health insurance obstacles; vi) counseling services for families. In this study, healthcare facilities with stroke services were preferred in stroke care, while optimal stroke care consisted of four main components that had to work together: health workers in health facilities, stroke survivors, family as successors of care in community settings, and the availability of health insurance facilities. In principle, the most important party in this situation was the family, including the nuclear or extended family; they could be the determinant in saving the lives of stroke survivors.